Diversion requirement estimation for paddy rice irrigation systems. - De Vera, Maximo R. Ph D.
A methodology for estimating the diversion requirement of lowland rice is presented using a cropping pattern based on rainfall distribution and dependable streamflow in the Bicol River basin. The case study involves some 8,000 hectares to be irrigated. Results of the study showed decadal irrigation diversion requirement varying from 0.07 to 1.76 liters/second/ha depending upon effective rainfall and crop growth stage. These figures are useful for system design and operation including water management.